2011
DOI: 10.2174/187152711794480429
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Natural Products in the Discovery of New Drug Candidates for the Treatment of Neurodegenerative Disorders II: Alzheimers Disease

Abstract: The present review is part II in a series (part I focuses on Parkinson's Disease) that addresses the value of natural product chemistry in the discovery of medicines for the treatment of neurodegenerative disorders. Data reviewed document that a host of products from plant species and derivatives have neuroprotectant effects in vitro and in vivo. In addition, besides neuroprotection, natural products also demonstrate biological effects that target biochemical pathways underlying associated symptoms of neurdegn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 271 publications
4
46
0
Order By: Relevance
“…Recently, natural plants extracts and their bio-active compounds has also been demonstrated to moderate the levels of cyclic nucleotide through inhibition of phosphodiesterases (Rahimi et al, 2010). In recent years, there is an unprecedented development in herbal medicines and these are gaining popularity day by day for the treatment of various neurodegenerative disorders including Alzheimer's disease (Divino da Rocha et al, 2011;Howes and Houghton, 2003;Shu, 1998). Herbal PDE inhibitors are under clinical development for the treatment of Alzheimer's disease.…”
Section: Q4mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, natural plants extracts and their bio-active compounds has also been demonstrated to moderate the levels of cyclic nucleotide through inhibition of phosphodiesterases (Rahimi et al, 2010). In recent years, there is an unprecedented development in herbal medicines and these are gaining popularity day by day for the treatment of various neurodegenerative disorders including Alzheimer's disease (Divino da Rocha et al, 2011;Howes and Houghton, 2003;Shu, 1998). Herbal PDE inhibitors are under clinical development for the treatment of Alzheimer's disease.…”
Section: Q4mentioning
confidence: 99%
“…During last decade various pharmaceutically active compounds/extracts come from the plants origin and shown beneficial effect in treatment of Alzheimer's disease and other cognitive disorders (Currais et al, 2014;Divino da Rocha et al, 2011).…”
Section: Therapeutic Potential Of Natural Plants In Alzheimer's Dismentioning
confidence: 99%
“…CP extracts also protected neuronal cells against glutamate-induced toxicity by modulating glutamate receptor function. In addition, the CP extracts protected neuronal cells by virtue of their free radical scavenging properties, reducing lipid peroxidation, and also by their ability to induce the antioxidant enzyme catalase [68,72-75]. In addition, aqueous extracts of CP seed have dose-dependent cholinergic activity, thereby improving memory performance [68].…”
Section: Jyotishmati (Celastrus Paniculatus)mentioning
confidence: 99%
“…Several natural products already evaluated for their efficacy in treating AD have been previously been summarized in literature [45,46]. Since recent clinical trials suggested tau-based therapies may be more effective than anti-Aβ treatments for patients already presenting AD symptoms, the relative paucity of tau-reducing agents needs to be addressed.…”
Section: Natural Products As Tau Targeting Agentsmentioning
confidence: 99%